Successful Treatment with Selpercatinib for Ectopic Cushing’s Syndrome Due to Medullary Thyroid Cancer - Oskar Ragnarsson; Marta Piasecka; Andreas Hallqvist (Current Oncology, 2022)
Selpercatinib, a RET kinase inhibitor, is an effective treatment for patients with medullary thyroid cancer with RET mutations. In this paper, we present the case of a 62-year-old man with ectopic Cushing’s syndrome due to medullary thyroid cancer who received treatment with selpercatinib. Six months later, all the cushingoid features had resolved, and s-calcitonin had decreased from 580 pmol/L to 3.5 pmol/L (normal < 3). After further 6 months, s-calcitonin had normalized (1.5 pmol/L), and radiological evaluation showed a profound tumour volume reduction. We are aware of two other cases where treatment with selpercatinib has also been successful. Thus, selpercatinib may be a promising treatment alternative in patients with ectopic Cushing’s syndrome due to medullary thyroid cancer, especially when other treatment options are ineffective or not tolerated.